2020
DOI: 10.31545/intagr/113259
|View full text |Cite
|
Sign up to set email alerts
|

ABA alleviated soybean seedling stress exposed to UV-C radiation

Abstract: In order to understand the roles of abscisis acid in soybean exposed to UV-C radiation, soybean seedlings were exposed to UV-C radiation and ABA was applied. The chlorophyll content, active oxygen metabolism and flavonoids content of soybean seedlings were investigated. The present study revealed that UV-C radiation significantly attenuated the chlorophyll content and suppressed PSII activity. It was observed that the contents of H 2 O 2 , malondialdehyde and O 2 were markedly increased, and the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In contrast, genotype C24 showed increased POD, APX, and GPX activities exposed to UV-B radiation (3.9 kJ m −2 , 4 d). UV-C radiation-induced enhancement of SOD and POD activities was also reported in G. max L. [ 130 ]. Seedlings of G. max L. grown under UV-C light with 0.284 mW cm −2 intensity (20 min d −1 ) resulted in enhanced activity of CAT, SOD, and POD that was further upregulated with exogenous application of AsA (10 mg L −1 ) [ 130 ].…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, genotype C24 showed increased POD, APX, and GPX activities exposed to UV-B radiation (3.9 kJ m −2 , 4 d). UV-C radiation-induced enhancement of SOD and POD activities was also reported in G. max L. [ 130 ]. Seedlings of G. max L. grown under UV-C light with 0.284 mW cm −2 intensity (20 min d −1 ) resulted in enhanced activity of CAT, SOD, and POD that was further upregulated with exogenous application of AsA (10 mg L −1 ) [ 130 ].…”
Section: Antioxidant Metabolism and The Detoxification Of Ros Undementioning
confidence: 62%
“…Tripathi et al [ 129 ] observed increased contents of O 2 •− , H 2 O 2 , MDA, and higher EL in T. aestivum L. seedlings exposed to two levels of UV-B radiation: ambient (8.6 kJ m −2 d −1 ) and enhanced (ambient + 2.8 kJ m −2 d −1 ). G. max L. plants grown under UV-C light with 0.284 mW cm −2 intensity (20 min d −1 ) resulted in remarkably higher O 2 •− , H 2 O 2, and MDA contents [ 130 ]. Four hours of UV-B radiation causes higher levels of EL, MDA, and O 2 •− contents in Morus alba seedlings under dark conditions [ 131 ].…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%